Media capture with Chinese characteristics: Changing patterns in Hong Kong's news media system. (August 2018) - Frisch, Nicholas; Belair-Gagnon, Valerie; Agur, Colin
In the Special Administrative Region of Hong Kong, a former British territory in southern China returned to the People's Republic as a semi-autonomous enclave in 1997, media capture has distinct characteristics. On one hand, Hong Kong offers a case of media capture in an uncensored media sector and open market economy similar to those of Western industrialized democracies. Yet Hong Kong's comparatively small size, close proximity, and broad economic exposure to the authoritarian markets and politics of neighboring Mainland China, which practices strict censorship, place unique pressures on Hong Kong's nominally free press. Building on the literature on media and politics in Hong Kong post-handover and drawing on interviews with journalists in Hong Kong, this article examines the dynamics of media capture in Hong Kong. It highlights how corporate-owned legacy media outlets are increasingly deferential to the Beijing government's news agenda, while social media is fostering alternative spaces for more skeptical and aggressive voices. This article develops a scholarly vocabulary to describe media capture from the perspective of local journalists and from the academic literature on media and power in Hong Kong and China since 1997.